IMPACTS OF HOT IN-PLACE RECYCLING TECHNIQUES IN PAKISTAN - Azad, Salahuddin (European Scientific Journal, ESJ, 2015)
A hot in-place recycling (HIR) technique was employed for the first time on Lahore-Islamabad Motorway in 2005 to rehabilitate sections where the rut depth was about 40 mm. Since HIR technology was new to Pakistan, research was carried out to study the effects of recycled wearing course of pavement.It was accomplished by comparing structural adequacy of pavement and material characterization before and after recycling.Analysis of recycled HMA wearing course indicated a reduction in modulus for a mix that was very stiff and aged prior to recycling. Relative degradation of the HMA wearing course was observed; however, it remained close to standard specifications specified by Executing Agency National Highway Authority (NHA). The research enhanced awareness of HIR among local engineers and contractors.